A Sixty-Year Research and Development of Trichosanthin, a Ribosome-Inactivating Protein - Lu, Jia-Qi; Wong, Kam-Bo; Shaw, Pang-Chui (Toxins, 2022)
Tian Hua Fen, a herbal powder extract that contains trichosanthin (TCS), was used as an abortifacient in traditional Chinese medicine. In 1972, TCS was purified to alleviate the side effects. Because of its clinical applications, TCS became one of the most active research areas in the 1960s to the 1980s in China. These include obtaining the sequence information in the 1980s and the crystal structure in 1995. The replication block of TCS on human immunodeficiency virus in lymphocytes and macrophages was found in 1989 and started a new chapter of its development. Clinical studies were subsequently conducted. TCS was also found to have the potential for gastric and colorectal cancer treatment. Studies on its mechanism showed TCS acts as an rRNA N-glycosylase (EC 3.2.2.22) by hydrolyzing and depurinating A-4324 in α-sarcin/ricin loop on 28S rRNA of rat ribosome. Its interaction with acidic ribosomal stalk proteins was revealed in 2007, and its trafficking in mammalian cells was elucidated in the 2000s. The adverse drug reactions, such as inducing immune responses, short plasma half-life, and non-specificity, somehow became the obstacles to its usage. Immunotoxins, sequence modification, or coupling with polyethylene glycerol and dextran were developed to improve the pharmacological properties. TCS has nicely shown the scientific basis of traditional Chinese medicine and how its research and development have expanded the knowledge and applications of ribosome-inactivating proteins.